Implementation of Algorithm C4.5 in Predicting Learning Readiness - Kosal Dharany (Etunas, 2023)
This paper discusses the implementation of the C4.5 algorithm in predicting learning readiness. Algorithm C4.5 is a machine learning technique that is often used to generate decision tree-based classification models. This study aims to develop a predictive model of learning readiness using the C4.5 algorithm. The data used in this study is secondary data obtained from the results of filling out the questionnaire by students. The stages in model development include data processing, making decision trees, and model evaluation. The results of the study show that the model developed using the C4.5 algorithm can predict learning readiness with fairly high accuracy. It is hoped that the results of this research can become a reference for the development of decision support systems in the education sector.